The structure of post/long COVID fatigue syndrome. Prospects for correction - Polina I. Kuznetsova; Marine M. Tanashyan; Anton A. Raskurazhev; Kira Ia. Zaslavskaya (Терапевтический архив, 2023)
Aim. To study the features of post-COVID asthenic syndrome and evaluate the effectiveness of the drug containing the succinic acid complex with trimethylhydrazinium in its treatment.